2021
DOI: 10.3390/ma14247723
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Ukrainian Volcanic Tuffs from the Khmelnytsky Region with the Theoretical Analysis of Their Application in Construction and Environmental Technologies

Abstract: (1) The mineral deposits are the base resources of materials used in building and environmental engineering applications, especially available locally. Two wells of volcanic tuff deposits in the Khmelnytsky region of Ukraine were investigated in this regard. (2) Physical-mechanical, chemical, and mineralogical analyses of the core samples were carried out. (3) The tuff samples were characterized by visible colour, low compressive strength (4.34–11.13 MPa), and high water absorption (30%). The dominant minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Iron-rich natural materials such as volcanic tuff, some kaolins, zeolites, and others that contain hematite (Fe 2 O 3 ) have shown a higher adsorption capacity for heavy metals compared to those materials that do not contain them or contain them in very low concentrations. So, for example, the sorption capacity of Mn 2+ by iron-containing tuff is more than 8.5 mg/g, and by basalt, it is 4.3 mg/g [12,13]. In addition, in the research study that compared the Ni 2+ sorption capacity of different kaolins, it was found that with hematite content in kaolin over 3.5%, the sorption capacity was approximately 2.5 times higher [14].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Iron-rich natural materials such as volcanic tuff, some kaolins, zeolites, and others that contain hematite (Fe 2 O 3 ) have shown a higher adsorption capacity for heavy metals compared to those materials that do not contain them or contain them in very low concentrations. So, for example, the sorption capacity of Mn 2+ by iron-containing tuff is more than 8.5 mg/g, and by basalt, it is 4.3 mg/g [12,13]. In addition, in the research study that compared the Ni 2+ sorption capacity of different kaolins, it was found that with hematite content in kaolin over 3.5%, the sorption capacity was approximately 2.5 times higher [14].…”
Section: Introductionmentioning
confidence: 93%
“…The diffractograms were interpreted using the ICCD PDF2+-2003 database (The International Centre for Diffraction Data) and the Match! V.1.9a software (Crystal Impact, Materials Park, OH, USA) [13,41].…”
Section: Study Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Запитання, які стосуються розгляду специфіки глобалізації у контексті музики та культури, находять відображення в наукових працях сучасності, f а саме поглиблене вивчення цих питань здійснено у роботах Л. Тан [11] і Т. Каблової [3]. Особливе вивчення форм культурної взаємодії та питання ідентичності можна знайти в роботі Ю. Трач [7]. Аналіз феномену діалогу в музичній комунікації, включений у контекст філософсько-культурологічної парадигми, представлений у дослідженні А. Тормахової [6].…”
unclassified